Association of Modified Geriatric Nutrition Risk Index and Handgrip Strength With Survival in Cancer: A Multi-Centre Cohort Study - Xie, Hailun; Ruan, Guotian; Zhang, Heyang; Zhang, Qi; Ge, Yizhong; Song, Mengmeng; Zhang, Xi; Lin, Shiqi; Liu, Xiaoyue; Liu, Yuying; Zhang, Xiaowei; Li, Xiangrui; et al. (Frontiers in Nutrition, 2022)
Background: This study aimed to explore the value of combining the modified geriatric nutrition risk index (mGNRI) and handgrip strength (HGS) in the prognosis assessment of cancer. Methods: This multicenter, prospective cohort study, enrolled 5,607 cancer patients from 27 medical centers across 17 provinces in China between June 2012 and December 2019. The primary outcome was overall survival. Secondary outcomes included the Karnofsky Performance Scale (KPS) score, Patient-Generated Subjective Global Assessment (PG-SGA) score, cachexia, and admission 90-day outcome. A composite prognostic score (mGNRI-HGS score) was developed based on the mGNRI and HGS. The Kaplan–Meier method was used to draw the survival curve, and log-rank analysis was used to estimate the survival rate. The Cox proportional hazards model was used to investigate the associations of the mGNRI, HGS or mGNRI-HGS score with risk of mortality among the cancer patients, adjusted for potential confounders. Results: A low mGNRI (HR = 0.99, 95%CI = 0.98-0.99, p < 0.001) and low HGS (HR = 0.99, 95%CI = 0.98-0.99, p = 0.001) were associated with an increased risk of mortality. A severe mGNRI-HGS score was independently associated with reduced survival. Compared with patients with normal scores, the risk of mortality among the patients with moderate and severe mGNRI-HGS scores was 28.8% and 13.3% higher, respectively. Even within the same pathological stage, it presented significant gradient prognostic stratification. Additionally, a low mGNRI-HGS score was also independently associated with a higher risk of low KPS (p<0.001), high PGSGA (p<0.001), cachexia (p<0.001), and adverse admission 90-day outcome (p<0.001). Conclusions: The mGNRI and HGS may be useful predictors of long-term prognosis in cancer patients. The combination of the two methods provides effective prognostic stratification for cancer patients and could predict physical frailty, malnutrition, and cachexia.